2022
DOI: 10.3389/fphys.2022.1032020
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the physiological status in professional basketball players using NESA neuromodulation treatment during different types of microcycles in season: A preliminary randomized clinical trial

Abstract: The purpose of the study was to describe and compare recovery status after official basketball competition in players who underwent NESA neuromodulation treatment (NNT) in weeks with one or two matches. The recovery parameters of 12 professional male basketball players (mean ± SD, age: 20.6 ± 2.7 yr; height: 197.8 ± 11.7 cm; and body mass: 89.0 ± 21.2 kg) that competed in the LEB Plata (Spanish third division) were monitored 2 days after match-play over 6 weeks, and included: 1) the Hooper Test, which combines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Where benefits in sleep quality like our study were also recorded were in those where the intervention was oriented towards education in sleep habits [69], or in the prescription of a physical exercise pattern [70]. These results are also consistent with the findings of previous experimental studies, in which an exercise modality like our study was observed with cognitive tasks/engagement in cognitively impaired older adults [71,72].…”
Section: Discussionsupporting
confidence: 91%
“…Where benefits in sleep quality like our study were also recorded were in those where the intervention was oriented towards education in sleep habits [69], or in the prescription of a physical exercise pattern [70]. These results are also consistent with the findings of previous experimental studies, in which an exercise modality like our study was observed with cognitive tasks/engagement in cognitively impaired older adults [71,72].…”
Section: Discussionsupporting
confidence: 91%
“…Cranial electrotherapy stimulation (CES) has been demonstrated to decrease negative emotions and choice reaction times, which can impair sport performance. In recent years, a new kind of noninvasive neuromodulation technique called NESA (Spanish name Neurestimulación superficial aplicada) has been gaining attention in autonomic nervous system treatment and sleep changes [16,17] as a part of daily preventive treatment and training.…”
mentioning
confidence: 99%